Konseling Realitas dalam Mengatasi Fenomena LGBT pada Remaja di Era Society 5.0 - Al Af Gani, Nasrullah Jamaludin; Ningsih, Anita; MS, Taufiqurohman (FKIP Universitas Islam Jember, 2024)
The development of media technology has a significant impact on individual perceptions of LGBT, especially in the era of society 5.0. The development of LGBT deviant behavior is very worried by the community, considering that lately more and more young generations have been exposed to this deviant behavior. This study aims to get an overview of the impact of technological developments on the perception of LGBT individuals. This study uses library research. Literature research involves theoretical research and reference references that are inseparable from scientific literature. Data collection uses the documentation method by reading related literature sources. The analysis uses descriptive analysis. The results of this study show that the development of media technology has a significant impact on the perception of LGBT individuals, especially in the era of society 5.0. The development of media platforms, such as social media platforms, has played a crucial role in shaping the perception of LGBT individuals and their experiences.